Portugal : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Securities Regulation, and Insurance Regulation. (IMF Staff Country Reports; Country Report ;, 2006)
Portugal's financial system is sound, well-managed and competitive, with shorter-term risks and vulnerabilities well contained, and with the system buttressed by a strong financial policy framework. Portuguese banks' profitability, asset quality, and solvency have held up well in recent years, despite a difficult operating environment. Nevertheless, household debt levels are well above the EU average, and corporate debt levels are also high, although bank credit to firms has been growing moderately in recent years. The government should continue to carefully monitor the key risk areas.